ISOLATION KLEBSIELLA Sp. AT BALI CATTLE BASED ON LEVEL OF MATURITY AND BREEDING LOCATION AND THE PATTERN OF SENSITIVITY AGAINST ANTIBACTERIAL - Ramaditya, Nyoman Anandiya; Tono PG, Ketut; Suarjana, I Gusti Ketut; Besung, I Nengah Kerta (Buletin Veteriner Udayana, 2018)
Research has been conducted to know the number bacterial isolates of Klebsiella sp . from bali cattle in terms of the level of maturity and the breeding location, also its sensitivity to the antibiotic there are ampicillin, sulfamethoxazole, and oxytetracycline. 120 bali cattle's nasal swabs consisting of calves, heifers, and adult cattle which are breeding on highland and lowland has been used as the isolates in this research. The obtained nasal swab was isolated and identified, then proceed with the sensitivity test. Bacterial of Klebsiella sp. has been found in calves were nine isolates (45%), heifers were six isolates (30%), and adult cattle were five isolates (25%). While based on the breeding location in the lowland found 13 isolates (65%) and highland found seven isolates (35%). In the sensitivity test results were obtained for the antibiotic ampicillin all isolates were sensitive (100%). sulfamethoxazole resistant four isolates (20%), intermediate two isolates (10%), and sensitive 14 isolates (70%). Oxytetracycline resistant seven isolates (35%), intermediate two isolates (10%), and sensitive 11 isolates (55%). The results showed that differences in the level of maturity and breeding location of bali cattle can affect the distribution of bacteria Klebsiella sp.